Perancangan Monitoring Suhu dan Kelembaban pada Kumbung Jamur Berbasis Internet of Things - Andre, Hanalde; Pratama, Faldo Demi; Pahlevi, Moh Reza; Afif, Muhammad; Fitri, Suci; Pratama, Rizki Wahyu; Hikmatullah, Muhammad Rizky (ELECTRON Jurnal Ilmiah Teknik Elektro, 2022)
Oyster mushroom cultivation is very popular among rural and urban communities, both on a small, medium and industrial scale. Oyster mushroom cultivation requires controlling temperature and humidity in mushroom kumbung to get optimal mushroom body growth. In the fruiting body formation phase requires a temperature between 27⁰C-29⁰C with humidity between 70%RH-90%RH. Along with the rapid development of technology, currently monitoring and controlling temperature and humidity can be done automatically remotely using the NodeMCU ESP8266 based on the Internet of Things. Measurement of temperature and humidity using the DHT22 sensor. The acquisition of measurement data is sent to the ANTARES platform using an internet-connected ESP8266. Monitoring temperature and humidity can be seen on ANTARES. Temperature and humidity control using a 12 Volt DC water pump. When the measurement results exceed the desired temperature range and the humidity is less than the desired range, the pump will turn on to stabilize the temperature and humidity again. From the results of testing the tool, it is obtained that the appropriate measurement results are obtained and the pump also turns on if the temperature and humidity are not as desired.